Pengaruh Jenis Komposter dan Waktu Pengomposan terhadap Pembuatan Pupuk Kompos dari Activated Sludge Limbah Industri Bioetanol - Wianthi Septia Witasari; Khalimatus Sa'diyah; Mohammad Hidayatulloh (Jurnal Teknik Kimia dan Lingkungan, 2021)
Side product of the waste water treatment plant in the bioethanol industry produces solid waste in the form of activated sludge.This waste can cause problems if not handled properly. Among them are reducing the nutrient content in the soil and polluting clean water sources when they enter river bodies. Activated sludge waste from the anaerobic biodigester process in the bioethanol industry can be used as organic fertilizer by composting. The purpose of this study was to determine the effect of composter design and composting time in making compost from activated sludge of bioethanol industrial waste on the content of compost produced. In composting process used an EM4 as bioactivator. The composter design used is an aerated composter and a non-aerated composter. The composting time used is blank, week 1, week 2, week 3 and week 4. From the analysis, it was found that the physical characteristics of compost were temperature, pH, humidity, C organic, total N, total P, total K, and theC / N ratio according to SNI 19-7030-2004. The use of aerated and non aerated design composters produces quality compost that meets SNI 19-7030-2004. The longer composting time will provide better quality compost.